Powder metallurgy and advanced materials selected papers from the 5th International Conference on Powder Metallurgy & Advanced Materials, RoPM&AM 2017, 17-20 September, Cluj-Napoca, Romania - Marinca, Traian Florin; Neamțu, Bogdan Viorel; Popa, Florin (Materials research proceedings ;, 2018)
The book presents recent advances in the following fields: Theoretical aspects, characterization and applications of powder and PM products. New developments in powder production and processing. Functional Materials. Nanomaterials and Nanotechnologies. Health, Safety and Environmental Aspects of Particulates. Keywords: Powder Metallurgy, Powder Characterization, Functional Materials, Nanomaterials, Health Aspects of Particulates, Environmental Aspects of Particulates, Microwires in Cellulose Matrix, Multi-layer Steel, Reactive Mechanical Milling, Green Synthesis of Nanoparticles, Linear Homopo.